Understanding the determinants of user choice in ride-hailing motorcycle services: evidence from Indonesia - Remba Yanuar Efranto; Muhammad Rajab Rahmatan Hidayah (Urban, Planning and Transport Research)
The expansion of ride-hailing motorcycle services has transformed urban transportation in Indonesia, offering convenience and affordability. However, misalignment between service features and user expectations remains a challenge. This study employs conjoint analysis to identify the most valued attributes among users of online motorcycle taxi platforms. A total of 200 respondents evaluated 12 orthogonal stimuli based on nine key attributes: timeliness, delivery speed, fare, vehicle cleanliness, payment options, driver communication, courtesy, travel insurance, and application interface. Results indicate that users prefer services that include penalties for late pickup, drivers selecting optimal routes, standardized cleanliness, eight payment methods, a fare of USD 0.11/km, mandatory communication, and a courteous driver demeanor. The driver courtesy requirement was the most influential factor, followed by cleanliness, communication, and punctuality. While preferred levels were consistent across genders, variations in importance values were observed. This study contributes to the body of knowledge by highlighting the cultural and operational factors shaping user preferences in emerging ride-hailing markets, offering insights that extend beyond Indonesia’s context. It provides empirical evidence for integrating user-centric attributes into service design to enhance adoption and retention.